PENGARUH NHT TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA VIII MTs KHULAFAURRASYIDIN PADA ZAT ADITIF DAN ADIKTIF - Yanto, Irwanda As; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe main goals of this study were 1) to determine whether there was a significant difference between achievements of students taught using NHT and conventional model, 2) to determine effect size of NHT model on studenstâ€™s achievement on additive and addictive substance material class VIII MTs Khulafaur Rasyidin. Quasi experimental was used as a form of research with design â€œnonequivalent control groupâ€. The sample was students of VIII D as experiment class and VIII C as control class. The essay test, interview and closed observation sheet was used as instrument of this research to collecting data. According to U-mann Whitney test using SPSS 16, the value of asymp.sig (2-tailed) was 0,02 (0,02<0,05).Therefore, there was a significant difference of student achievement was taught by using cooperative model NHTâ€™s type (numbered head together) with student achievement was taught by using conventional learning to the material additive and adictive substance and getting score asymp.sig (2-tailed) was 0,002 (0,002<0,05) on score test of studentsâ€™ activity in first meeting and 0,003 (0,003<0,05) on score test of studentsâ€™ activity in second meeting. Therefore, there was a different of studentsâ€™ activity in those classes. Effect size was 0,72 which categorical as moderate criteria.Â Keywords: cooperative model numbered head together, the result of study, activity, additive and adictive substance.